The non-clinical burden of febrile seizures: a systematic review - Marangoni, Maria Beatrice; Corsello, Antonio; Cozzi, Laura; Agostoni, Carlo; Santangelo, Andrea; Milani, Gregorio Paolo; Dilena, Robertino (Frontiers in Pediatrics, 2024)
Febrile seizures (FS) can be frightening for parents, even though they are usually harmless. Various questionnaires have been used to assess parental reactions and awareness about FS, revealing insufficient knowledge. Studies have shown that educational interventions significantly reduce parental concerns, improve knowledge, and promote better first-aid measures. Providing clear information and emotional support to parents is important to reduce their concerns and improve FS management.Healthcare providers should give comprehensive information about FS, including the risk of recurrence, and provide clear instructions on their management.The economic impact of FS includes direct and indirect costs. Studies have shown a decrease of hospitalizations and associated costs due to improved clinical adherence to guidelines, which also reduces the inappropriate use of healthcare resources. This systematic review provides a comprehensive overview of the existing literature on parental anxiety and education about FS, as well as their economic impact, aiming at identifying areas for improvement in the management of FS and providing valuable insights for healthcare providers and policymakers to better address the non-clinical burden of this condition.